Techno-Economic Analysis of a Flexible Process Concept for the Production of Transport Fuels and Heat from Biomass and Renewable Electricity - Habermeyer, Felix; Kurkela, Esa; Maier, Simon; Dietrich, Ralph-Uwe (Frontiers in Energy Research, 2021)
Different processes have been proposed to meet the global need for renewable fuel. The Biomass to Liquid process (BtL) converts biomass via the Fischer-Tropsch route to hydrocarbon chains that can be refined to transport fuel. With the addition of electrolytic hydrogen to the Power and Biomass to Liquid process (PBtL), the carbon efficiency can be increased relative to the BtL process. It was shown in previous studies that the PBtL concept has an economic edge over BtL when cheap electricity is available to maximize the fuel yield. In this study, a techno-economic analysis is conducted for a hybrid process concept which can switch operation modes from electrolysis enhanced to only biomass conversion. In case studies the effect of the Fischer-Tropsch conversion, H2/CO ratio of the Fischer-Tropsch feed and the biomass feed rate in the electrolysis enhanced mode are analyzed. Every process configuration is modeled based on experimentally validated unit models from literature in the commercial software Aspen Plus and analyzed using DLR’s software tool TEPET. For a 200 MWth biomass input plant, production costs of 1.08 €2019/l for the hybrid concept with a carbon efficiency of 53.3 % compared to 0.66 €2019/l for BtL with 35.4 % and 1 €2019/l for PBtL with 61.1 % were found based on the Finnish day-ahead market for the base case. The net production cost for the hybrid concept can be decreased by 0.07 €2019/l when a Fischer-Tropsch H2/CO ratio of 1.6 instead of 2.05 is used.